Pregunta
upstudy study bank question image url

\[ \begin{array}{l} \left(\frac{y}{2}\right)^{n}=\left(\frac{\sum}{2}\right)^{n-1} \\ 8=n-1 \\ \therefore n=9 \end{array} \] CTIVTTIES/ASSESSMENTS Classwork/Homework 1. \( k+1 ; k-1 ; 2 k-5 ; \ldots \) are the first three terms of a geometric sequence, where \( k<0 \) : (a) Calculate the value of \( k \). (b) Determine the sequence. (c) Determine the general term of the seog (d) Find the 10 th term. (c) Which ferm of the sequence is -59649 ? 2. Determine an expression for the \( n^{\text {th }} \) term for a geometric sequence whose \( 3^{\text {th }} \) term is -20 and the \( 6^{\text {th }} \) term is 160 . 3. \( x-4: x+2 ; 3 x+1: \ldots \) are the first three terms of a geometric sequence. Determine the general term of the sequence in terms of \( x \).

Ask by Hanson Howell. in South Africa
Jan 08,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

**Problem 1: Geometric Sequence** - **(a) Value of \( k \):** \( k = -2 \) - **(b) Sequence:** \( -1, -3, -9 \) - **(c) General Term:** \( a_n = -1 \cdot 3^{n-1} \) - **(d) 10th Term:** \( a_{10} = -19683 \) - **(e) Term Equal to -59649:** 11th term **Problem 2: Expression for the \( n^{\text{th}} \) Term** \[ a_n = -5 \cdot (-2)^{n-1} \] **Problem 3: General Term of the Sequence** \[ a_n = 4 \cdot \left(\frac{5}{2}\right)^{n-1} \]

Solución

Let's solve each part of the problem step by step. ### Problem 1: Geometric Sequence Given the first three terms of a geometric sequence: \( k+1, k-1, 2k-5 \) where \( k < 0 \). #### (a) Calculate the value of \( k \). In a geometric sequence, the ratio between consecutive terms is constant. Therefore, we can set up the following equation based on the ratios: \[ \frac{k-1}{k+1} = \frac{2k-5}{k-1} \] Cross-multiplying gives: \[ (k-1)^2 = (k+1)(2k-5) \] Expanding both sides: \[ k^2 - 2k + 1 = 2k^2 - 5k + 2k - 5 \] This simplifies to: \[ k^2 - 2k + 1 = 2k^2 - 3k - 5 \] Rearranging gives: \[ 0 = 2k^2 - 3k - 5 - k^2 + 2k - 1 \] \[ 0 = k^2 - k - 6 \] Factoring the quadratic: \[ 0 = (k - 3)(k + 2) \] Thus, \( k = 3 \) or \( k = -2 \). Since \( k < 0 \), we have: \[ k = -2 \] #### (b) Determine the sequence. Substituting \( k = -2 \) into the terms: 1. First term: \( k + 1 = -2 + 1 = -1 \) 2. Second term: \( k - 1 = -2 - 1 = -3 \) 3. Third term: \( 2k - 5 = 2(-2) - 5 = -4 - 5 = -9 \) Thus, the sequence is: \[ -1, -3, -9 \] #### (c) Determine the general term of the sequence. The common ratio \( r \) can be calculated as: \[ r = \frac{-3}{-1} = 3 \] The general term \( a_n \) of a geometric sequence is given by: \[ a_n = a_1 \cdot r^{n-1} \] Where \( a_1 = -1 \) and \( r = 3 \): \[ a_n = -1 \cdot 3^{n-1} \] #### (d) Find the 10th term. Substituting \( n = 10 \): \[ a_{10} = -1 \cdot 3^{10-1} = -3^9 \] Calculating \( 3^9 \): \[ 3^9 = 19683 \] Thus: \[ a_{10} = -19683 \] #### (e) Which term of the sequence is -59649? We need to find \( n \) such that: \[ -1 \cdot 3^{n-1} = -59649 \] This simplifies to: \[ 3^{n-1} = 59649 \] Calculating \( 3^{n-1} \): \[ 3^{n-1} = 3^{10} \quad \text{(since } 3^{10} = 59049 \text{)} \] Thus: \[ n - 1 = 10 \implies n = 11 \] ### Problem 2: Expression for the \( n^{\text{th}} \) term Given the \( 3^{\text{rd}} \) term is -20 and the \( 6^{\text{th}} \) term is 160. Let the first term be \( a \) and the common ratio be \( r \). The terms can be expressed as: \[ a r^2 = -20 \quad \text{(1)} \] \[ a r^5 = 160 \quad \text{(2)} \] Dividing equation (2) by equation (1): \[ \frac{a r^5}{a r^2} = \frac{160}{-20} \] This simplifies to: \[ r^3 = -8 \implies r = -2 \] Substituting \( r \) back into equation (1): \[ a (-2)^2 = -20 \implies 4a = -20 \implies a = -5 \] Thus, the general term is: \[ a_n = -5 \cdot (-2)^{n-1} \] ### Problem 3: General term of the sequence Given the first three terms: \( x-4, x+2, 3x+1 \). Setting up the ratio: \[ \frac{x+2}{x-4} = \frac{3x+1}{x+2} \] Cross-multiplying gives: \[ (x+2)^2 = (x-4)(3x+1) \] Expanding both sides: \[ x^2 + 4x + 4 = 3x^2 - 12x + x - 4 \] This simplifies to: \[ x^2 + 4x + 4 = 3x^2 - 11x - 4 \] Rearranging gives: \[ 0 = 2x^2 - 15x - 8 \] Using the quadratic formula: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} = \frac{15 \pm \sqrt{(-15)^2 - 4 \cdot 2 \cdot (-8)}}{2 \cdot 2} \] Calculating the discriminant: \[ = \frac{15 \pm \sqrt{225 + 64}}{4} = \frac{15 \pm \sqrt{289}}{4} = \frac{15 \pm 17}{4} \] Thus: \[ x = \frac{32}{4} = 8 \quad \text{or} \quad x = \frac{-2}{4} = -\frac{1}{2} \] Using \( x = 8 \): 1. First term: \( 8 - 4 = 4 \) 2. Second term: \( 8 + 2 = 10 \) 3. Third term: \( 3(8) + 1 = 25 \) The common ratio \( r \): \[ r = \frac{10}{4} = \frac{5}{2} \] The general term is: \[ a_n = 4 \cdot \left(\frac{5}{2}\right)^{n-1} \] Thus, the general term of the sequence in terms of

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To solve the first problem involving the geometric sequence with \( k+1 \), \( k-1 \), and \( 2k-5 \), we can set up the condition for a geometric sequence where the ratio between consecutive terms is constant. The ratio \( r \) can be expressed as: \[ r = \frac{k-1}{k+1} = \frac{2k-5}{k-1} \] Cross-multiplying and simplifying will lead to a quadratic equation in \( k \). After solving, you'll find that \( k = -3 \). This means the first three terms are \( -2 \), \( -4 \), and \( -11 \). For the \( n^{\text{th}} \) term of this sequence, we can generalize it as \( a_n = a_1 \cdot r^{n-1} \), and for \( k = -3 \) and our derived terms, you can express the common ratio \( r \) and find the \( nth \) term formula. Now, addressing the second problem about the \( n^{th} \) term where the \( 3^{rd} \) term is -20 and the \( 6^{th} \) term is 160. The general formula for the \( nth \) term is given by: \[ a_n = a_1 \cdot r^{n-1} \] We can use the information given for the \( 3^{rd} \) and \( 6^{th} \) terms to set up a system of equations, allowing us to find both \( a_1 \) and \( r \) to express the \( n^{th} \) term appropriately. For the third problem about the sequence \( x-4 \), \( x+2 \), and \( 3x+1 \): setting up the ratio conditions again yields a similar approach. You'll find the common ratio \( r \) between these terms and subsequently express the general term in terms of \( x \). Each example here reflects foundational concepts in geometric sequences and allows for application of algebraic techniques to derive findings and formulate patterns!

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad